GeoCapabilities1 and curriculum leadership: balancing the priorities of aim-based and knowledge-led curriculum thinking in schools. Issue 4 (2nd October 2017) - Uhlenwinkel, Anke; Béneker, Tine; Bladh, Gabriel; Tani, Sirpa; Lambert, David
ABSTRACT: The small-scale research presented in this paper was conducted as part of the GeoCapabilities project. Though originating in the Anglophone world, the project attempts to address the purposes and values of geography education internationally. Using the idea of "powerful disciplinary knowledge" the project asks what geography has to offer that helps young people develop the human capabilities they need in order to live a life that they consider valuable. In this paper, we explore the challenges and opportunities presented by GeoCapabilities in several European national contexts. We asked selected teachers and teacher educators in four different countries (Finland, Germany, The Netherlands and Sweden) what role they thought geography plays in enhancing students' "human potential." Despite marked differences relating to the legal and structural background in each country we found major similarities in teachers' and teacher educators' curriculum thinking in relation to geography's contribution to the future well-being of their students.